CHEAP THE THEORY OF CREATING SOLAR PANELS - Rajabov, Nurmuhammed (Физико-технологического образование, 2023)
This article covers the theory of how to create cheap and convenient solar panels. In the integration of energy systems based on renewable energy sources into the network, their technical, resource, economic and ecological indicators are shown, taking into account the specific aspects of the considered network